THE RELATIONSHIP BETWEEN EURATOM AND THE UNITED KINGDOM AFTER BREXIT - Maria-Cristina SOLACOLU (Challenges of the Knowledge Society)
On 29 March 2017 the United Kingdom invoked Article 50 of the Treaty on European Union, triggering the process of withdrawal from the Union – the first Member State to ever do so. This historic moment also marked the beginning of negotiations, with representatives of the two entities focusing primarily on provisions related to the single market and citizens’ rights. One topic that has been seldom brought up during these talks is the future of the United Kingdom in the European Atomic Energy Community (Euratom). The purpose of this paper is to determine whether a Member State’s withdrawal from the European Union entails leaving Euratom and to identify some of the options the United Kingdom has with regard to either its continued membership of the latter or the forging of a new type of relationship with it. Issues of particular interest are the jurisdiction of the Court of Justice of the European Union over matters relating to nuclear research, materials and technology, the freedom of movement that is granted to nuclear specialists and the fact that Euratom and the European Union share their institutional organisation. Failure to reach an agreement on these subjects, which are likely to hinder negotiations, would have important short-term and long-term consequences that also warrant a closer examination.